Four new species and new records of Micropeneta Pic, 1921 (Coleoptera: Tenebrionidae: Gnathidiini) from the Oriental and Papuan Regions, including a checklist and an identification key - Schawaller, Wolfgang; Bellersheim, Aron (Zootaxa, 2022)
The genus Micropeneta Pic, 1921 (Tenebrionidae: Gnathidiini) was known so far by seven species in the Oriental Region. Newly collected material is presented herein including four species new to science: M. alabaca sp. n., M. kinabaluca sp. n., both from Borneo, M. laotica sp. n. from Laos, and M. papuana sp. n. from West Papua. The material shows that the genus is also distributed in Indochina and on New Guinea. The species of Micropeneta are characterised by the male head with a pair of distinct glabrous cephalic horns or shorter processes; some species possess additionally the anterior margin of the male pronotum with a pair of teeth or flat swellings, or the anterior part of pronotum with a broad impression. A checklist for all species and an identification key (suitable for males only) is added.